Microglia Actively Regulate the Number of Functional Synapses - Ji, Kyungmin; Akgul, Gulcan; Wollmuth, Lonnie P.; Tsirka, Stella E. (PLOS ONE, 2013)
Microglia are the immunocompetent cells of the central nervous system. In the physiological setting, their highly motile processes continually survey the local brain parenchyma and transiently contact synaptic elements. Although recent work has shown that the interaction of microglia with synapses contributes to synaptic remodeling during development, the role of microglia in synaptic physiology is just starting to get explored. To assess this question, we employed an electrophysiological approach using two methods to manipulate microglia in culture: organotypic hippocampal brain slices in which microglia were depleted using clodronate liposomes, and cultured hippocampal neurons to which microglia were added. We show here that the frequency of excitatory postsynaptic current increases in microglia-depleted brain slices, consistent with a higher synaptic density, and that this enhancement ensures from the loss of microglia since it is reversed when the microglia are replenished. Conversely, the addition of microglia to neuronal cultures decreases synaptic activity and reduces the density of synapses, spine numbers, surface expression of AMPA receptor (GluA1), and levels of synaptic adhesion molecules. Taken together, our findings demonstrate that non-activated microglia acutely modulate synaptic activity by regulating the number of functional synapses in the central nervous system.